Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1007/s00425-004-1446-8
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid contents and transport in oilseed rape (Brassica napus L.) under different nitrogen conditions

Abstract: Oilseed rape (Brassica napus L.) needs very high nitrogen fertilizer inputs. Significant amounts of this nitrogen are lost during early leaf shedding and are a source of environmental and economic concern. The objective of this study was to investigate whether the remobilization of leaf amino acids could be limiting for nitrogen use efficiency. Therefore, amino acid concentrations were analyzed in subcellular compartments of leaf mesophyll cells of plants grown under low (0.5 mM NO3-) and high (4 mM NO3-) nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 44 publications
8
84
1
1
Order By: Relevance
“…In the reproductive stage, these nitrogen compounds are depredated and the amino acids transported to sink tissues. Because the production of GS1 and AAPs, which are involved in whole plant partitioning of nitrogen, is induced in the reproductive stage (Miflin and Habash 2002;Tilsner et al 2005), it is possible that expression of the genes encoding these enzymes is affected by the development of sink tissues. In this report, we observed a reduction in amino acid content during leaf-stage progression and an increase in amino acid content after removal of the reproductive structures, supporting these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…In the reproductive stage, these nitrogen compounds are depredated and the amino acids transported to sink tissues. Because the production of GS1 and AAPs, which are involved in whole plant partitioning of nitrogen, is induced in the reproductive stage (Miflin and Habash 2002;Tilsner et al 2005), it is possible that expression of the genes encoding these enzymes is affected by the development of sink tissues. In this report, we observed a reduction in amino acid content during leaf-stage progression and an increase in amino acid content after removal of the reproductive structures, supporting these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that while the N content in stems varied at flowering between the fertilization levels, it was similar at maturity (Stahl et al 2015). Tilsner et al (2005) showed that the phloem loading of amino acids was not limiting for nitrogen remobilization efficiency, and they hypothesized that sink capacity rather than source strength was the main bottleneck for N remobilization in rapeseed. The final sink capacity of rapeseed can be enhanced primarily through the improvement of the yield components per se.…”
Section: Nitrogen Remobilization Efficiency In Rapeseedmentioning
confidence: 99%
“…Nitrogen fertilisation can be used for nutritional improvement of the human diet by increasing and maintaining protein and essential amino acid contents (Thanapornpoonpong et al, 2008). According to Tilsner et al (2005) under low N supply, the amino acid contents are comparable at all leaf ages and decrease slightly from young to mature leaves, while higher N supply also causes an overall increase in amino acid content (Atanasova, 2008).…”
Section: Introductionmentioning
confidence: 99%